Chile : Selected Issues. (IMF Staff Country Reports; Country Report, 2006)
The report gives details of the economic analysis for the implementation of Chile's inflation targeting framework. It reviews the current state of liquidity in the Chilean fixed-income markets and developments and impediments to the supply of corporate bonds to the market. The paper considers a number of microstructure issues, transparency in the Over-the-Counter (OTC) market, addresses the role of public debt in facilitating development of the financial markets, and discusses a potential debt management framework that would support the development of a liquid public debt market.